PELATIHAN MENJADI PELATIH OUTBOND PADA KELOMPOK PKK GUNA MEMBANGUN KARAKTER, KREATIFITAS, DAN RASA TANGGUNG JAWAB TERHADAP ANAK - Ahadiati Rohmatiah; Siti Suharni; Wira Ganet Aribowo (Universitas Merdeka Madiun, 2025)
The issue of limited community involvement, particularly among PKK mothers, in children's educational activities is a key concern in strengthening character education. The Training of Trainer for Outbound Capacity Building program offers a solution by enhancing the capacity of PKK mothers in Bader Village to serve as facilitators of children’s outbound activities. This program employed an experiential learning method, emphasizing hands-on learning through outdoor educational games. The activity was conducted by a community service team and KKN students from Universitas Merdeka Madiun and included stages of preparation, implementation, and evaluation. The results show a significant increase in participants' knowledge, facilitation skills, and confidence in leading children’s groups. The training also fostered collaboration, leadership, and responsibility. In conclusion, the program effectively empowered PKK mothers as community change agents and holds strong potential for sustainability with continued support from local institutions.